KONTRIBUSI DAN EFEKTIVITAS PENERIMAAN PAJAK REKLAME TERHADAP PAJAK DAERAH DI KABUPATEN TABALONG PERIODE 2017-2020 - Muzain Arifin; Akhmad Sayudi; Ayu Oktaviani (Universitas Lambung Mangkurat, 2021)
ABSTRACTThis research..aims to find out..and..analyze the level..contribution and effectiveness of tax revenue advertising to taxes regions in Tabalong Regency in 2017-2020. The type of data used is quantitative data, such as target data and advertisement tax realization from 2017-2020.Theresults..research..that..obtained..is..tax contribution..advertising to taxes regions still very less, meanwhile to effectiveness already classified effective.